Correcting for tissue nitrogen excretion in multiple breath washout measurements - Kane, Mica; Rayment, Jonathan H.; Jensen, Renee; McDonald, Reginald; Stanojevic, Sanja; Ratjen, Felix (PloS one, 2017)
Nitrogen excreted from body tissues impacts the calculation of multiple breath nitrogen washout (MBWN2) outcomes. The aim of this study was to determine the effect of tissue N2 on MBWN2 outcomes in both healthy subjects and patients with CF and to assess whether it is possible to correct for tissue N2. The contribution of tissue N2 to MBWN2 outcomes was estimated by comparing MBWN2-derived functional residual capacity (FRCN2) to FRC measured by body plethysmography (FRCpleth) and by comparing MBW outcome measures derived from MBWN2 and sulfur hexafluoride MBW (MBWSF6). Compared to plethysmography and MBWSF6, MBWN2 overestimated FRC and lung clearance index (LCI). Application of mathematical tissue N2 corrections reduced FRCN2 values closer to FRCpleth in health and reduced LCIN2 in both health and CF, but did not explain all of the differences observed between N2-dependent and -independent techniques. Use of earlier washout cut-offs could reduce the influence of tissue N2. Applying tissue N2 corrections to LCIN2 measurements did not significantly affect the interpretation of treatment effects reported in a previously published interventional trial. While tissue N2 excretion likely has an impact on MBWN2 outcomes, better understanding of the nature of this phenomenon is required before routine correction can be implemented into current MBWN2 protocols.